Free Country : a tale of the children's crusade - Gaiman, Neil; Litt, Toby, 1968-; Kwitney, Alisa, 1964-; Delano, Jamie (DC Comics/Vertigo, 2015)
"For the first time, the two-issue miniseries THE CHILDREN'S CRUSADE, written by Neil Gaiman, Alisa Kwitney and Jamie Delano, are collected - and with them, a new chapter written by Toby Litt that completes the tale as Gaiman originally envisioned it. When several children go missing in a small English town, the Dead Boy Detectives are on the case. A series of strange and unexpected twists take them to Free Country, a place that dates back a millennia, where children never grow old and are free from the abuse and tyranny of adults. But Free Country is failing, and what it needs is the strength of five innately powerful children - including the young sorcerer Timothy Hunter - to restore their uncanny world to what it once was. This hardcover collects THE CHILDREN'S CRUSADE #1 and THE CHILDREN'S CRUSADE #2, written by Gaiman with cowriters Alisa Kwitney and Jamie Delano. A brand-new middle chapter written by DEAD BOY DETECTIVES writer Toby Litt and drawn artist Peter Gross (THE BOOKS OF MAGIC, THE UNWRITTEN) completes this compelling tale of ancient history, stolen dreams and lost children. Also featuring a new introduction by Gaiman, plus new cover art by DEAD BOY DETECTIVES artist Mark Buckingham"--